2009
DOI: 10.1007/s11661-009-9941-y
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Approach for Prediction of Hot Tearing

Abstract: Shrinkage, imposed strain rate, and (lack of) feeding are considered the main factors that determine cavity formation or the formation of hot tears. A hot-tearing model is proposed that will combine a macroscopic description of the casting process and a microscopic model. The micromodel predicts whether porosity will form or a hot tear will develop. Results for an Al-4.5 pct Cu alloy are presented as a function of the constant strain rate and cooling rate. Also, incorporation of the model in a finite element m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 18 publications
0
29
2
Order By: Relevance
“…In the SKK criterion, [31] three possible phenomena may happen during the last stage of solidification. Firstly, the liquid flow can adequately compensate for the solidification shrinkage and thermal contraction, and therefore no cavities are formed.…”
Section: Hot Tearing Predictions By the Skk Criterionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the SKK criterion, [31] three possible phenomena may happen during the last stage of solidification. Firstly, the liquid flow can adequately compensate for the solidification shrinkage and thermal contraction, and therefore no cavities are formed.…”
Section: Hot Tearing Predictions By the Skk Criterionmentioning
confidence: 99%
“…Apart from experimental approaches, many non-mechanical and mechanical criteria have been proposed to predict hot tearing. [14,30,31] Suyitno et al [16] have evaluated eight commonly used criteria by implementing them into a thermomechanical model of DC casting. It was found that the RDG criterion [32] could predict the hot tearing susceptibility for all studied process parameters, although it was not able to accurately predict whether hot tears will form during DC casting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once the stresses and strains in the material are known, the parameters related to the occurrence of casting defects can be calculated. The model used to calculate the micro-porosity in the material and the susceptibility of the material to hot tearing relies on the Suyitno-Kool-Katgerman model, which was developed specifically for use with numerical models of the casting process [13]. The model starts by stating the conservation equation for three phases, each associated with a volume fraction:…”
Section: Prediction Of Hot-tearingmentioning
confidence: 99%
“…Finally, it is a combination of both non-mechanical and mechanical criteria, such as RDG (Rappaz-Drezet-Gremaud) and Suyitno criteria [13,14] , which investigate the pressure drop over the mush zone reaching a critical value for cavity nucleation or the microporosity exceeding a critical size. In this work, an experiment was carried on a 234-t heavy steel ingot where a shrinkage crack band was found in the ingot upper centerline.…”
mentioning
confidence: 99%